1995
DOI: 10.1016/0167-4943(95)00653-3
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of chronic nimodipine treatment on behavioral dysfunctions of aged rats exposed to perinatal ethanol treatment

Abstract: The long-term effects of prenatal and early postnatal ethanol exposure were assessed in adult (5-month), aged (24-month), and senescent (30-month) rats on non-aggressive intermale social behavior, and on black-white discrimination and spatial learning behaviors. Furthermore, the effects of chronic application of the Ca(2+) channel blocker nimodipine, which reportedly improves behavioral function in aging, were studied on the ethanol-induced behavioral deficits during aging. The results showed that the perinata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Overall, the findings reported here are consistent with the literature in which social behavior has been studied in aged rats (Andersen et al, 1999; Hunt et al, 2011; Markel et al, 1995; Salchner et al, 2004; Shoji and Mizoguchi, 2011; Soffié and Bronchart, 1988), thereby replicating a substantial decline in overall social behavior during senescence (Exps. 1 and 2) and extending those findings to female Fischer 344 rats (Exp.…”
Section: 0 Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Overall, the findings reported here are consistent with the literature in which social behavior has been studied in aged rats (Andersen et al, 1999; Hunt et al, 2011; Markel et al, 1995; Salchner et al, 2004; Shoji and Mizoguchi, 2011; Soffié and Bronchart, 1988), thereby replicating a substantial decline in overall social behavior during senescence (Exps. 1 and 2) and extending those findings to female Fischer 344 rats (Exp.…”
Section: 0 Resultssupporting
confidence: 90%
“…Studies have demonstrated that aged rodents exhibit alterations in a number of behavioral domains, including impaired cognitive function (Barrientos et al, 2012; Foster, 2012; Gallagher and Rapp, 1997; Nomura and Okuma, 1999; Rosenzweig and Barnes, 2003), increased anxietylike (Boguszewski and Zagrodzka, 2002; Darwish et al, 2001; Frussa-Filho et al, 1991; Hunt et al, 2011; Imhof et al, 1993; Miyagawa et al, 1998) and depressive-like behaviors (Kiss et al, 2012; Moretti et al, 2011), decreased locomotor activity (Gage et al, 1984; Godbout et al, 2008; Hunt et al, 2011), and importantly, impaired social interaction (Andersen et al, 1999; Hunt et al, 2011; Markel et al, 1995; Mencio-Wszalek et al, 1992; Salchner et al, 2004; Shoji and Mizoguchi, 2011; Soffié and Bronchart, 1988). Aged male rats (14–30-months-old) have been reported to exhibit reduced play behavior (Soffié and Bronchart, 1988), fewer social interactions (Markel et al, 1995; Salchner et al, 2004), less social investigation (Andersen et al, 1999), and to engage in less contact with conspecifics (Hunt et al, 2011) relative to adolescent or young adult rats (1.5–6-months-old).…”
Section: 0 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-binding proteins calbindin-D 28K and calreticulin in cerebral cortex [120]. Nimodipine improved motor performance on balance, hanging and climbing tests and age-related alterations in limb coordination were delayed [128]. Nimodipine also enhances cerebral blood flow and T-and L-type Ca 2?…”
Section: Ion Channels and General Brain Agingmentioning
confidence: 97%
“…channel blockers (e.g., the L-type Ca 2? channel antagonist, nimodipine) enhance associative and spatial learning in old animals [120,[127][128][129].…”
Section: Ion Channels and General Brain Agingmentioning
confidence: 99%